2015
DOI: 10.1021/acsami.5b04231
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide Transparent Hybrid Film and Its Ultraviolet Shielding Property

Abstract: Herein, we first reported a facile strategy to prepare functional Poly(vinyl alcohol) (PVA) hybrid film with well ultraviolet (UV) shielding property and visible light transmittance using graphene oxide nanosheets as UV-absorber. The absorbance of ultraviolet light at 300 nm can be up to 97.5%, while the transmittance of visible light at 500 nm keeps 40% plus. This hybrid film can protect protein from UVA light induced photosensitive damage, remarkably.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 29 publications
0
64
0
Order By: Relevance
“…The E g values also provided a fair compare of the overall optical performance among various UV-absorbing materials. The results showed that the UV-shielding efficacy of these two types of lignin nanoparticles was comparable to prevalent metal oxide nanoparticles and other emerging biopolymer nanoparticles such as polydopamine and melanin [13, 15, 25, 26]. …”
Section: Resultsmentioning
confidence: 99%
“…The E g values also provided a fair compare of the overall optical performance among various UV-absorbing materials. The results showed that the UV-shielding efficacy of these two types of lignin nanoparticles was comparable to prevalent metal oxide nanoparticles and other emerging biopolymer nanoparticles such as polydopamine and melanin [13, 15, 25, 26]. …”
Section: Resultsmentioning
confidence: 99%
“…Every part of solar light also has its special application. As Xie reported, it has been proved that prolonged exposure to UV irradiation would result in acute and chronic health effects on the skin, eyes, and immune system of humans . Consequently nanoparticles that shield UV light (200 nm–400 nm) can be used in sunscreen .…”
Section: Figurementioning
confidence: 99%
“…It should be noted that our PVA/SiMoA composite films present a nice balance between high visible transparency and UV‐shielding performance, while many approaches to designing UV‐protection materials often enhanced in just one kind of optical properties. For instance, PVA/S‐GO films exhibit a high UV‐shielding of ~97%, yet a relatively low visible transparency (only ~44%) . Similarly, PVA/TiO 2 films have a high UV‐shielding of ~98%, whereas the visible transparency is relatively low, only ~40% .…”
Section: Resultsmentioning
confidence: 99%